Answers

2015-04-01T18:11:46+05:30
P/q = √(p - x^2)/√(q - x^2) p^2/q^2 = (p - x^2)/(q - x^2) Cross multiply (p^2)*(q - x^2) = (q^2)*(p - x^2) p^2*q - p^2*x^2 = q^2*p - q^2*x^2 p^2*q - q^2*p = p^2*x^2 - q^2*x^2 pq(p - q) = x^2*(p^2 - q^2) pq(p - q) = x^2*(p + q)(p - q) pq = x^2*(p + q) X^2 = pq/(p + q)
3 4 3
  • Brainly User
2015-04-01T18:27:55+05:30
p/q = √(p - x^2)/√(q - x^2) p^2/q^2 = (p - x^2)/(q - x^2) Cross multiply (p^2)*(q - x^2) = (q^2)*(p - x^2) p^2*q - p^2*x^2 = q^2*p - q^2*x^2 p^2*q - q^2*p = p^2*x^2 - q^2*x^2 pq(p - q) = x^2*(p^2 - q^2) pq(p - q) = x^2*(p + q)(p - q) pq = x^2*(p + q) X^2 = pq/(p + q)
0